Adhesion protein networks reveal functions proximal and distal to cell-matrix contacts. (April 2016) - Byron, Adam; Frame, Margaret C
Graphical abstract: Highlights: Cell adhesion to the extracellular matrix (ECM) is vital for multicellular life. Complexes of structural and signalling proteins link the ECM to the cytoskeleton. Adhesion signalling networks are complex, diverse, dynamic and tightly regulated. Some adhesion proteins perform unexpected functions away from cell-matrix contacts. Nuclear roles for adhesion proteins have been revealed in diseases such as cancer. Abstract : Cell adhesion to the extracellular matrix is generally mediated by integrin receptors, which bind to intracellular adhesion proteins that form multi-molecular scaffolding and signalling complexes. The networks of proteins, and their interactions, are dynamic, mechanosensitive and extremely complex. Recent efforts to characterise adhesions using a variety of technologies, including imaging, proteomics and bioinformatics, have provided new insights into their composition, organisation and how they are regulated, and have also begun to reveal unexpected roles for so-called adhesion proteins in other cellular compartments (for example, the nucleus or centrosomes) in diseases such as cancer. We believe this is opening a new chapter on understanding the wider functions of adhesion proteins, both proximal and distal to cell-matrix contacts.